2002
DOI: 10.1113/jphysiol.2002.025452
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of rat colonic afferent fibres by 5‐HT3 receptors

Abstract: The gastrointestinal tract contains most of the body's 5‐hydroxytryptamine (5‐HT) and releases large amounts after meals or exposure to toxins. Increased 5‐HT release occurs in patients with irritable bowel syndrome (IBS) and their peak plasma 5‐HT levels correlate with pain episodes. 5‐HT3 receptor antagonists reduce symptoms of IBS clinically, but their site of action is unclear and the potential for other therapeutic targets is unexplored. Here we investigated effects of 5‐HT on sensory afferents from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 34 publications
8
90
2
Order By: Relevance
“…Previous studies demonstrated the presence of metabotropic 5-HT receptors in intestinal afferent neurons and suggest that only a subgroup express 5-HT 3 receptors (Hillsley and Grundy, 1998; Hicks et al, 2002). In addition to differential expression of 5-HT receptors, the onset and duration of 5-HT effects differed with stimulation of metabotropic receptors, causing a slower and longer-lasting stimulation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies demonstrated the presence of metabotropic 5-HT receptors in intestinal afferent neurons and suggest that only a subgroup express 5-HT 3 receptors (Hillsley and Grundy, 1998; Hicks et al, 2002). In addition to differential expression of 5-HT receptors, the onset and duration of 5-HT effects differed with stimulation of metabotropic receptors, causing a slower and longer-lasting stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…Although these mediators play an important role in changes attributable to injury and inflammation, the effects of 5-HT on colon sensory neurons provides a mechanism by which physiological stimuli can trigger enhanced responses in normal tissue. Mucosal stimuli trigger 5-HT release from enteroendocrine cells, which in turn activates intrinsic and extrinsic primary afferent neurons within the gut wall (Pan and Gershon, 2000;Hicks et al, 2002). Given the apparent expression of TRPV1 in nearly all C57BL/6 colon DRG neurons, and the generation of spontaneous action potentials at normal body temperature after exposure to 5-HT, the activation of peripheral afferents may contribute to sensation and even conscious perception of visceral stimuli in the uninflamed gut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are excited by stroking the mucosa with very light von Frey hairs (10 mg) and are strongly activated by 5-hydroxytryptamine or 5-HT3 agonists. 68 Spinal mucosal afferents are more abundant in lumbosacral than thoracolumbar spinal pathways, 46 but the detailed structure of their endings…”
Section: Spinal Mucosal Afferentsmentioning
confidence: 99%